ARGUMENTATION SKILL IN STEM-EDP WORKSHEET FOR HIGH SCHOOL STUDENTS: VALIDITY ASPECT - Remanda Arya Wisutama; Nurul Fitriyah Sulaeman; Zulkarnaen Zulkarnaen (JURNAL PEMBELAJARAN FISIKA, 2023)
Argumentation skill need to be enhanced through contextual problem with integrated STEM (Science, Technology, Engineering, and Mathematics). This study aims to develop worksheet of STEM-EDP based worksheets that focus on students' arguments on the topic of climate change. This research is a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) focused on ADD stages. Worksheet designs are prepared by containing STEM indicators accompanied by worksheets that refer to aspects of Toulmin's Argument Pattern. The validity by two lecturers of Physics Education obtained content feasibility aspects (90.00%), linguistic aspects (91.25%), presentation aspects (93.75%), and graphical aspects (83.75%). The conclusion is that STEM-EDP based worksheets fall into the very valid category with a validity value of 89.69%. STEM-EDP based worksheets that focus on students' arguments on the topic of climate change are feasible to implement in classroom learning.